Minimally Invasive Video-Assisted Thyroidectomy (MIVAT) in western world: a systematic review from 2015 to 2022 - Del Rio, Paolo; De Gennaro, Flavia; Bonati, Elena; Loderer, Tommaso; Cozzani, Federico (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Since its first description Minimally Invasive Video-Assisted Thyroidectomy (MIVAT) has spread especially in Western Countries, and it has arisen as a feasible and safe treatment in selected patients undergoing lobectomy or total thyroidectomy. Our review aimed at collecting all the studies published in Western Countries (Europe and America) from 2015 to 2022 to evaluate the outcomes and complication rates of MIVAT technique. Methods: The search terms were “mininvasive thyroidectomy”, “video-assisted thyroidectomy”, “mini-invasive thyroidectomy”, “minimally invasive thyroidectomy”, ” MIVAT”, “endoscopic thyroidectomy”. Studies were selected according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) parameters and enrolled respecting pre-established inclusion and exclusion criteria. Results: Out of 552 screened studies, 4 retrospective observational articles and 4 prospective observational studies were considered suitable. The total number of patients was 4489. Complication rate of MIVAT was low and comparable with complication rate of conventional thyroidectomy described in literature. Conclusions: In conclusion MIVAT is a well-established technique in Continental Europe and North America, with a good safety profile and low invasiveness; further studies are needed to evaluate subjective aesthetic results of this technique.